PERAN KEPUASAN KERJA DALAM MEMEDIASI PERSEPSI KEADILAN DAN BEBAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA SATUAN KERJA BIRO LOGISTIK POLDA JATENG - Soco Adi Wibowo; fania mutiara savitri; Euis Soliha (Jurnal Litbang Polri, 2022)
This study aims to determine the factors that can affect the organizational commitment of the Logistics Bureau of the Central Java Police. The independent variables in this study are perceptions of Justice and workload. The dependent variable in this study is organizational commitment with job satisfaction as a mediating variable. This study uses quantitative methods by using questionnaires to collect the required data. The sample consisted of 100 employees of the Central Java Police Logistics Bureau. In this study, the analysis used is regression analysis using the SPSS 23 application. The analysis used includes research instrument testing, coefficient of determination, hypothesis testing and Sobel test. The results of this study indicate that the perception of Justice has an effect on job satisfaction and organizational commitment, while workload has no effect on job satisfaction and organizational commitment. Job satisfaction has been shown to mediate the effect of perceived Justice on organizational commitment.